Features of epithelial-mesenchymal transition in ectopic endometrium in patients with extragenital endometriosis of various localizations. Observational study - Eugeniu Cazacu; Eremei Zota; Mariam A. Vardanyan; Radu Niguleanu; Ruslan Pretula; Aleksandra V. Asaturova; Larisa S. Ezhova; Alina S. Badlaeva (Гинекология, 2024)
Background. Epithelial-mesenchymal transition (EMT) is a conserved mechanism in the process of morphogenesis and organogenesis. EMT provides cells with migratory and invasive properties, which is a necessary condition for the formation of endometrioid heterotopias.